Climate Change and Eutrophication: A Short Review - Nazari Sharabian, M.; Ahmad, S.; Karakouzian, M. (Engineering, Technology & Applied Science Research, 2018)
Water resources are vital not only for human beings but essentially all ecosystems. Human health is at risk if clean drinking water becomes contaminated. Water is also essential for agriculture, manufacturing, energy production and other diverse uses. Therefore, a changing climate and its potential effects put more pressure on water resources. Climate change may cause increased water demand as a result of rising temperatures and evaporation while decreasing water availability. On the other hand, extreme events as a result of climate change can increase surface runoff and flooding, deteriorating water quality as well. One effect is water eutrophication, which occurs when high concentrations of nutrients, such as nitrogen and phosphorus, are present in the water. Nutrients come from different sources including agriculture, wastewater, stormwater, and fossil fuel combustion. Algal blooms can cause many problems, such as deoxygenation and water toxicity, ultimately disrupting normal ecosystem functioning. In this paper, we investigate the potential impacts of climatic factors affecting water eutrophication, how these factors are projected to change in the future, and what their projected potential impacts will be.